Revisiting dislocation reactions and their role in uniaxial deformation of copper single crystal micro-pillars. (23rd May 2019) - Mishra, Ashish; Alankar, Alankar
Abstract: The present work focuses on the discrete dislocation dynamics simulations performed for analyzing various dislocation reactions in copper single crystals during uniaxial tensile deformation. The dislocation dynamics simulations were carried out with initial random distribution of Frank–Read sources. The crystals were subjected to tensile loading along [1 0 0], [1 1 1], [1 1 2] and [2 1 3] crystallographic axes. The hardening behavior of a metal single crystal is controlled, to a large extent, by dislocation interactions leading to junction formation and cross-slip. The interactions occurring between the dislocations, formation of junctions, occurrence of cross-slip, their contribution to hardening and softening, and dislocation density evolution were analyzed. Also, analysis was carried out to identify the number of occurrences of different reactions as a function of crystallographic orientations of loading axes. The strength due to self-hardening and latent-hardening dislocation reactions on the deformation of crystal was then analyzed. We have attempted to analyze the hardening and softening caused by various reactions including cross-slip. The self and latent hardening coefficients do not appear to depend on the crystallographic orientation of loading axes and are generally in agreement with the previous studies.